PENERAPAN METODE QIRA’AH DALAM PEMBELAJARAN BAHASA ARAB SISWA SMA MUHAMMADIYAH DISAMAKAN MAKASSAR - Muh. Alwi; Fatmawati Fatmawati (Universitas Muhammadiyah Makassar, 2018)
This study aims to determine the application of the Qira'ah method in Arabic Language Learning at senior High School Muhammadiyah of Makassar, knowing the inhibiting factors and the teacher's efforts to improve Arabic learning. This research uses qualitative methods and using survey methods in data collection. To complete the data, in this researchdata collection techniques used are interviews, observation, and documentation. The results of this study indicate that the application of the qira'ah method in learning Arabic at senior High School Muhammadiyah of Makassar. Students need to be combined with other methods, such as the Gramatika Tarjamah method, the Lingual Audio method or the direct method. Caused by the inhibiting factors such as students who do not know hijaiyah letters, lack of interest in learning Arabic, and the weak ability of students to master mufradat, so the application of the Qira'ah method needs to be combined with other methods. And as for the efforts made by the teacher in improving the learning of Arabic students by providing additional learning, giving special attention and the need for emphasis on students in memorizing vocabulary.Keywords: Application, Qira'ah method, Arabic